Peran Stres Kerja Dalam Memediasi Pengaruh Kontrak Psikologis Dan Beban Kerja Terhadap Keinginan Karyawan Untuk Keluar Dari Organisasi: Studi Pada Sebuah Klinik Kecantikan - Mahaiswari, Anak Agung Sagung Agung Sri; Rahyuda, Agoes Ganesha (E-Jurnal Manajemen; Vol 4 No 4 (2015), 2015)
The aim of this study isto examine the role of occupational stress in mediating the effect of psychological contract and the workload of the desire of workers to get out of the organization. This study was conducted on employees in doc_ignga beauty clinic, which has four branches, two branches in Denpasar, Tabanan, and Gianyar. Samples in this study were taken with a saturated sample method. Data were collected using a survey method with interviews and questionnaires. Survey respondents as many as 34 employees . he results of this study were (1) the psychological contract affects the desire to come out directly and indirectly through the stress of work, and (2) the workload affects the desire to come out directly and indirectly through the stress of work.This indicates that the psychological contract, workload, and stress can increase the desire to work out.
Keywords: kontrak psikologis; beban kerja; stres kerja; keinginan untuk keluar